1999
DOI: 10.1002/(sici)1097-0142(19991215)86:12<2602::aid-cncr4>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Larger and more invasive colorectal carcinoma contains larger amounts of plasminogen activator inhibitor type 1 and its relative ratio over urokinase receptor correlates well with tumor size

Abstract: BACKGROUND Considering recent findings that both urokinase plasminogen activator receptor (uPAR) and plasminogen activator inhibitors (PAIs) are involved in tumor growth through an urokinase‐type plasminogen activator (uPA) activity‐independent mechanism, the relation between the presence of these factors in tumor tissue and the clinicopathologic variables in colorectal carcinoma was reevaluated. METHODS In 100 colorectal carcinoma patients, antigen levels of u‐PA, uPAR, and PAI‐1 and PAI‐2 were assayed in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 46 publications
(83 reference statements)
3
32
1
Order By: Relevance
“…Tumour cells simultaneously secrete proteases (uPA) and their inhibitors (PAI-1), and the balance between the two precisely regulates the level of extracellular proteolysis, thus either promoting or suppressing angiogenesis (Folkman et al, 2001). It is likely that excess PAI-1 decreases cell adhesion to the extracellular matrix by interfering with uPAR binding to vitronectin, thus facilitating cell invasion and migration (Abe et al, 1999). Other reports have also indicated that excess PAI-1 plays an important role in tumour growth and metastasis by stimulating angiogenesis (McMahon et al, 2001;Bajou, 2002;Devy et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cells simultaneously secrete proteases (uPA) and their inhibitors (PAI-1), and the balance between the two precisely regulates the level of extracellular proteolysis, thus either promoting or suppressing angiogenesis (Folkman et al, 2001). It is likely that excess PAI-1 decreases cell adhesion to the extracellular matrix by interfering with uPAR binding to vitronectin, thus facilitating cell invasion and migration (Abe et al, 1999). Other reports have also indicated that excess PAI-1 plays an important role in tumour growth and metastasis by stimulating angiogenesis (McMahon et al, 2001;Bajou, 2002;Devy et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In these processes, PAI-1 can bind to uPAR-bound uPA and results in internalization of the PAI-1:uPA:uPAR complex, leading to degradation of PAI-1 and uPA and recycle of uPAR on the cell surface (Nykjaer et al 1997). Many clinical and experimental studies have proved that the high expression of uPA, uPAR, and PAI-1 was closely related to the unfavorable prognosis of tumors (Harbeck et al 1999;Abe et al 1999;Knoop et al 1998). uPA, uPAR, and PAI-1 levels were considered as independent and signi®cant prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…----------------been shown to be the most substantial determinant of the overall survival rate in patients with colorectal cancer, 36) we focused on the role of the PA system and VEGF in the liver metastasis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%